Pengaruh Kemudahan dan Efisiensi Terhadap Penggunaan Mobile Banking Pembayaran UKT - Lydia Zabrina Miranda; Moch. Chairil Asmawan (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2025)
With the advent of mobile banking services, technological advancements have had a significant impact on the banking industry. Bill payments, fund transfers, and purchasing goods and services are just a few examples of the many financial operations that can be accelerated and simplified using mobile banking. The main objective of this study is to determine how much impact mobile banking has on the ease of students at the University of Muhammadiyah Surakarta (UMS) in making payments. Quantitative research using stratified random sampling procedures was conducted on 308 students from the Faculty of Teacher Training and Education (FKIP) UMS. This study found that the adoption of mobile banking is positively and significantly influenced by efficiency and convenience. Mobile banking is popular among students because of its ease of use, with features such as an easy-to-understand UI and simple navigation. Mobile banking is becoming increasingly popular because of its many benefits, including lower transaction costs and faster processing times. Convenience and efficiency are two major factors that students consider when deciding to use mobile banking for their financial activities, according to this study. The calculated F value is 211.473 with a significance level of 0.000, according to the results of the F test. This means that these two independent factors simultaneously significantly influence the use of mobile banking. To answer the needs of customers, especially students, this study highlights the importance of innovation in the development of technology-based financial services.